War and Peace in Islam - Louay M. Safi (International Institute of Islamic Thought, 1988)
Introduction Although the rules and principles pertaining to relations between Islamic and non-Islamic states date back to the early Madinan period, the Islamic classical doctrine of war and peace was developed by Muslim jurists (fuqaha) during the Abbasi era. The tenets of the doctrine can be found either in general law corpora under headings such as jihad, peace treaties, aman, or in certain special studies such as al Kharaj (land tax), al Siyar (biography/history), etc. The work of the Muslim jurists consists mainly of rules and principles concerning the initiation and prosecution of war, rules and principles that have been predicated on a specific perception of the role and objectives of the Islamic state in respect to other states. The purpose of this paper is twofold. On the one hand, the paper attempts to rebut the propositions of the classical doctrine of jihad, showing that these propositions were predicated on a set of legal rulings (ahkam shar'iyyah) pertaining to specific questions which arose under particular historical conditions, namely, the armed struggle between the Islamic state during the Abbasi era, and the various European dynasties. The paper further attempts to demonstrate that classical jurists did not intend to develop a holistic theory with universal claims. The paper aspires, on the other hand, to introduce a more comprehensive perception of war and peace which takes into account the Qur'anic and Prophetic statements in their totality. This new perception is then used to establish the fundamental objectives of war as well as the basic conditions of peace. To address the forgoing concerns, two approaches have been used. One is legalistic, deductively based on the principles of Islamic jurisprudence (usul al fiqh), comparable to that used by classical jurists. The other approach is historical, inductively concerned with examining the chronology of the ...